Dr. Bosun Tijani's inspiring visit to IITA: innovations for Nigeria's future! - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
In his mandate to support the nation's agenda, Dr. ‘Bosun Tijani, the Minister of Communications, Innovation, and Digital Economy of the Federal Republic of Nigeria, visits IITA. The plan is centered on leveraging technology to improve the desired outcome for the agricultural sector in Nigeria.